Advances in the Application of Transition-Metal Composite Nanozymes in the Field of Biomedicine - Huixin Wang; Chunfang Cheng; Jingyu Zhao; Fangqin Han; Guanhui Zhao; Yong Zhang; Yaoguang Wang (Biosensors, 2024)
Due to the limitation that natural peroxidase enzymes can only function in relatively mild environments, nanozymes have expanded the application of enzymology in the biological field by dint of their ability to maintain catalytic oxidative activity in relatively harsh environments. At the same time, the development of new and highly efficient composite nanozymes has been a challenge due to the limitations of monometallic particles in applications and the inherently poor enzyme-mimetic activity of composite nanozymes. The inherent enzyme-mimicking activity is due to Au, Ag, and Pt, along with other transition metals. Moreover, the nanomaterials exhibit excellent enzyme-mimicking activity when composited with other materials. Therefore, this paper focuses on composite nanozymes with simulated peroxidase activity that have been prepared using noble metals such as Au, Ag, and Pt and other transition metal nanoparticles in recent years. Their simulated enzymatic activity is utilized for biomedical applications such as glucose detection, cancer cell detection and tumor treatment, and antibacterial applications.